Celiac Disease Presenting as Hemolytic Anemia Mimic: A Case Report. Issue 1 (June 2020) - Siddiqui, Anjum; Khan, Ruhi
Celiac disease, an immune-mediated enteropathy, results from gluten ingestion in the form of wheat, rye, and barley in genetically susceptible individuals. It is a systemic disorder characterized by a variable combination of gluten-related signs and symptoms, and disease-specific antibodies in addition to enteropathy. The clinical presentation of celiac disease is extremely variable: a small proportion of patients presenting with severe gastrointestinal symptoms and malabsorption, and extraintestinal symptoms, and a large proportion having no symptoms at all. Owing to the varied clinical presentation, diagnosing celiac disease remains a challenge. We present a case of celiac disease presenting with severe anemia and clinical features suggestive of hemolytic anemia, making diagnosis even more difficult.